CD19 and POU2AF1 are Potential Immune-Related Biomarkers Involved in the Emphysema of COPD: On Multiple Microarray Analysis - Zhang DW; Ye JJ; Sun Y; Ji S; Kang JY; Wei YY; Fei GH (Dove Medical Press, 2022)
Da-Wei Zhang,1,2,* Jing-Jing Ye,1,2,* Ying Sun,1,2 Shuang Ji,1,2 Jia-Ying Kang,1,2 Yuan-Yuan Wei,1,2 Guang-He Fei1,2 1Department of Respiratory and Critical Care Medicine, First Affiliated Hospital of Anhui Medical University, Hefei, 230022, Anhui Province, People's Republic of China; 2Key Laboratory of Respiratory Diseases Research and Medical Transformation of Anhui Province, Hefei, 230022, Anhui Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Guang-He Fei, Department of Respiratory and Critical Care Medicine, First Affiliated Hospital of Anhui Medical University, Hefei, 230022, Anhui Province, People's Republic of China, Tel +86 551 6292 2013, Fax +86 551 6363 5578, Email guanghefei@126.comPurpose: Emphysema is the main cause of the progression of chronic obstructive pulmonary disease (COPD). This study aimed to identify the key genes involved in COPD-related emphysema.Patients and Methods: GSE76925 was downloaded from Gene Expression Omnibus database. Protein-protein interaction networks of differentially expressed genes (DEGs) between control and COPD groups were constructed to identify hub genes using Cytoscape. Diagnostic performance of hub genes was evaluated using receiver operating characteristic analysis. Correlation analysis was performed to identify the key genes by analyzing the relationship between the hub genes and lung function and computed tomography (CT) indexes of emphysema. COPD patients were then divided into two groups based on the median expression of key genes and DEGs between these two groups were identified. Enrichment analysis of DEGs and correlation analysis between key genes and the infiltration of the immune cells were also analyzed. Finally, the role of key genes was evaluated in a lung tissues dataset (GSE47460) and a blood dataset (GSE76705). Additionally, the expression of key genes was validated by quantitative real-time polymerase chain reaction and immunohistochemistry.Results: CD19 and POU2AF1 had diagnostic efficacy for COPD and were significantly correlated with lung function and CT indexes of emphysema. Enrichment and immune analyses revealed that CD19 and POU2AF1 were correlated with the B cells in COPD. These results were consistent in GSE47460. The expression of CD19 and POU2AF1 in blood was the opposite of that in lung tissues, and CD19 and POU2AF1 were both significantly upregulated in COPD lung tissues at both the mRNA and protein levels.Conclusion: CD19 and POU2AF1 may serve as key regulators of emphysema and contribute to the progression of COPD by regulating the B-cell immunology. Targeting B cells may be a promising strategy for treating COPD.Keywords: chronic obstructive pulmonary disease, emphysema, B cell, bioinformatics analysis